2021
DOI: 10.1016/j.jhepr.2021.100354
|View full text |Cite
|
Sign up to set email alerts
|

Control of APOBEC3B induction and cccDNA decay by NF-κB and miR-138-5p

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
(74 reference statements)
0
7
0
Order By: Relevance
“…These effectors exert anti-HBV function through interfering with HBV reverse transcription and replication, prompting cccDNA for degradation, or reducing replenishment of cccDNA pool. [28][29][30][31] In addition, we found that DF-006 upregulated toll-like receptor pathway genes including Tlr2 and Tlr3, activation of which has been shown to suppress HBV replication. [32] Of note, we found that induction of NF-κB-induced genes occurred in isolated hepatocytes as well as liver tissue.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…These effectors exert anti-HBV function through interfering with HBV reverse transcription and replication, prompting cccDNA for degradation, or reducing replenishment of cccDNA pool. [28][29][30][31] In addition, we found that DF-006 upregulated toll-like receptor pathway genes including Tlr2 and Tlr3, activation of which has been shown to suppress HBV replication. [32] Of note, we found that induction of NF-κB-induced genes occurred in isolated hepatocytes as well as liver tissue.…”
Section: Discussionmentioning
confidence: 74%
“…In assessing interferon‐stimulated genes (ISG)27 that are mediated indirectly or directly by NF‐κB and have anti‐HBV activity, we noted upregulation of Ddx58 (RNA sensor RIG‐I [ RIG‐I ]), Apobec3 , Isg20 , and Trex1 . These effectors exert anti‐HBV function through interfering with HBV reverse transcription and replication, prompting cccDNA for degradation, or reducing replenishment of cccDNA pool 28–31. In addition, we found that DF‐006 upregulated toll‐like receptor pathway genes including Tlr2 and Tlr3 , activation of which has been shown to suppress HBV replication 32…”
Section: Discussionmentioning
confidence: 83%
“…Signaling pathways are established targets in cancer therapy [ 177 ] and have previously drawn attention as targets for cancer prevention attenuating liver disease progression [ 178 , 179 ]. Host signaling-targeting approaches to battle chronic infection have been discussed [ 133 , 180 , 181 ] as they hold the potential to lower the genetic barrier of resistance to direct-acting antivirals. However, currently, only interferons are in clinical use targeting chronic viral hepatitis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, LTβR agonist 31G4D8 (antibody) and LIGHT-R228E mutein induces ROS production, resulting in cancer cell apoptosis [155]. Recently, it was shown that LTβR agonistic antibody BS1 initiates apolipoprotein B mRNA editing enzyme catalytic subunit 3B (APOBEC3B) expression through noncanonical NFκB signaling to suppress hepatitis B virus (HBV) replication [159][160][161].…”
Section: Specific Targeting Hvem and Ltβr Strategymentioning
confidence: 99%